A need for a simplified approach to venous thromboembolism prophylaxis in acute medical inpatients. - Howard, D (2007)
Venous thromboembolism (VTE) is a major cause of morbidity and mortality in the UK. Studies have shown that pulmonary embolism causes or contributes to approximately 1 in 10 hospital deaths of medical patients admitted to general hospitals in the UK (Lindblad B, Sternby NH, Bergqvist D. BMJ 1991; 302: 709-11), with pulmonary embolus being the most common preventable cause of hospital death. Thromboprophylaxis is safe, highly effective and cost effective, but despite various current clinical guidelines, physicians fail to prescribe prophylaxis for the majority of medical inpatients at risk of VTE. This article outlines the current evidence for VTE prophylaxis in medical patients and discusses the reasons behind the insufficient use of prophylaxis in the acute medical setting.